From oligonucleotide shapes to genomic SELEX: Novel biological regulatory loops - Gold, Larry (The National Academy of Sciences of the USA, 1997)
The SELEX method and oligonucleotide combinatorial chemistry discovery process yields high-affinity/high-specificity ligands for virtually any molecular target. Typically, the enormous starting libraries used in the SELEX process contain 10(14)–10(15) sequences. We now ask if the smaller sequences, complexity of extant organisms, and evolutionary history provide useful interactions between oligonucleotides and at least some unexpected targets. That is, do organisms contain a robust “linkage map” between their oligonucleotides and proteins and/or small molecules that enriches life?